EFFECT OF AGRONOMIC BIOFORTIFIATION WITH IODINE ON THE YIELD AND NUTRACEUTICAL QUALITY OF SALADETTE TOMATO (Solanum lycopersicum L.) - Cervantes Vázquez, Tomás Juan Álvaro; Preciado-Rangel, Pablo; Lagunes Fortiz, Erika; Vázquez Vázquez, Cirilo; Cervantes Vázquez, María Gabriela; Fortis Hernández, Manuel; Rueda Puente, Edgar (Chilean Journal of Agricultural & Animal Sciences, 2024)
Iodine is not considered an essential nutrient for terrestrial plants like tomato. However, it can increase the concentration of secondary metabolites as a reactive mechanism to oxidative stress in tomato fruit. In humans, iodine is essential for thyroid metabolism and the development of cognitive abilities, being associated with lower risks of certain types of cancer. The objective of this research was to evaluate the effect of foliar applications of iodine on the yield, commercial and nutraceutical quality, and iodine concentration in tomato fruits. The treatments were five increasing concentrations of potassium iodide (0, 5, 10, 15 and 20 µM L-1). The results showed that the foliar application of high doses of iodine improved crop yield, but had no influence on some commercial quality variables, such as soluble solids and firmness. Nutraceutical quality concentrations improved, except for lycopene content, which decreased with foliar applications of iodine. Therefore, iodine biofortification can be a viable alternative to improve the nutritional quality of tomato fruits, being a potential strategy to reduce or prevent iodine deficiency.